Luteolin promotes macrophage-mediated phagocytosis by inhibiting CD47 pyroglutamation - Zhiqiang Li; Xuemei Gu; Danni Rao; Meiling Lu; Jing Wen; Xinyan Chen; Hongbing Wang; Xianghuan Cui; Wenwen Tang; Shilin Xu; Ping Wang; Lei Yu; et al. (Translational Oncology, 2021)
‘Don't eat me’ signal of CD47 is activated via its interaction with SIRPα protein on myeloid cells, especially phagocytic cells, and prevents malignant cells from anti-tumor immunity in which pyroglutamate modification of CD47 by glutaminyl-peptide cyclotransferase-like protein (isoQC) takes an important part evidenced by our previous report that isoQC is an essential regulator for CD47-SIRPα axis with a strong inhibition on macrophage-mediated phagoctyosis. Therefore, we screened for potential isoQC inhibitors by fluorescence-activated cell sorting assay and identified luteolin as a potent compound that blocked the pyroglutamation of CD47 by isoQC. We further demonstrated that luteolin directly bound to isoQC using pull-down assay and isothermal calorimetric (ITC) assay. In consistency, we showed that luteolin markedly abrogated the cell-surface interaction between CD47 and SIRPα in multiple myeloma H929 cells and consequently promoted the macrophage-mediated phagocytosis. Collectively, our study discovered a promising lead compound targeting isoQC, luteolin, which functions distinctly from current CD47 antibody-based drugs and therefore may potentially overcome the clinical side effects associated with CD47 antibody treatment-induced anemia.